How does the antimicrobial stewardship provider role affect prospective audit and feedback acceptance for restricted antibiotics in a Canadian tertiary-care center? - Hammond, Keely M.; Kabbani, Dima; Doucette, Karen E.; Smith, Stephanie W.; Lau, Cecilia; Bains, Serena; Fong, Karen; Stewart, Jackson; Chen, Justin Z. (Infection control and hospital epidemiology, 2024)
Of 731 restricted antimicrobial prescriptions subject to antimicrobial stewardship program (ASP) prospective audit and feedback (PAF) over a 3-year period, 598 PAF recommendations (82%) were fully accepted. Physician auditors had an increased odds of PAF recommendation acceptance, reinforcing the complementary role of the ASP physician in the multidisciplinary ASP team.